PERILAKU PEDAGANG TERHADAP KEBERSIHAN LINGKUNGAN PASAR TRADISIONAL DI NAGARI PASAR BARU - Kasri, Zoni Putra; Ernawati, Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to describe the behavior of traders towards the cleanliness of the traditional market environment in Pasar Baru Nagari, Bayang sub-district, Pesisir Selatan Regency. This study uses a phenomenological qualitative approach, the location of this research is in the traditional market area, Nagari Pasar Baru, Bayang District, Pesisir Selatan Regency. The results showed that the majority of traders in Pasar Baru did not maintain the cleanliness of the market environment. The market environment is colored by the amount of garbage scattered around the market environment. This condition is caused by the lack of participation of traders in maintaining the cleanliness of the market environment. Such behavior of traders is motivated by the lack of awareness of traders in maintaining the cleanliness of their respective environments and traders assume that environmental cleanliness and market comfort are entirely the responsibility of cleaners and market managers. Traders assume that by paying a certain amount of fees, their responsibility for the waste of their respective merchandise just goes away